2018
DOI: 10.1177/0025802418797178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human pineal gland acetylserotonin O-methyltransferase immunoreactivity in suicide: A preliminary study

Abstract: Disorders of the serotonergic system are especially known to be present in the neurobiology of suicidal behavior. Studies investigating melatonin levels show that changes in pineal gland functions may also play a role in the pathogenesis of suicide. However, to our knowledge, there are no studies evaluating the activity of pinealocytes responsible for melatonin synthesis in suicide. This preliminary study aimed to investigate the relationship among pinealocyte, acetylserotonin O-methyltransferase (ASMT) immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…the recurrence and frequency of episodes which have a predictive value for suicide attempts (Pawlak et al, 2017). Moreover, lower melatonin levels have been significantly associated with completed suicides in post-mortem studies (Kurtulus Dereli et al, 2018) and this may further support our findings of more lethal suicide attempts and lower levels of melatonin in spring -summer, when there are less hours of darkness during which melatonin is produced in pinealocytes. Interestingly, melatonin results from the n-acetylatylation of 5-HT via the catalyzation of enzymes aralkylamine n-acetyltransferase (AANAT) and acetylserotonin O-methyltransferase (ASMT) that are regulated by clock-genes.…”
Section: Discussionsupporting
confidence: 81%
“…the recurrence and frequency of episodes which have a predictive value for suicide attempts (Pawlak et al, 2017). Moreover, lower melatonin levels have been significantly associated with completed suicides in post-mortem studies (Kurtulus Dereli et al, 2018) and this may further support our findings of more lethal suicide attempts and lower levels of melatonin in spring -summer, when there are less hours of darkness during which melatonin is produced in pinealocytes. Interestingly, melatonin results from the n-acetylatylation of 5-HT via the catalyzation of enzymes aralkylamine n-acetyltransferase (AANAT) and acetylserotonin O-methyltransferase (ASMT) that are regulated by clock-genes.…”
Section: Discussionsupporting
confidence: 81%
“…The secretory activity of melatonin was quantified and proved to be low in patients that have committed suicide. This is not enough to imply a direct and routine examination of the pineal gland during routine forensic autopsies, but it can provide a complementary argument for the neurobiological risk factors of suicide [86].…”
Section: Discussionmentioning
confidence: 99%
“…According to the reports, a decline in melatonin levels is observed in individuals with sleep difficulties, depression 12 , 13 , and suicide 13 - 15 . Arioz et al 16 have demonstrated that the administration of melatonin is associated with a reduction in depression-like behaviors.…”
Section: Introductionmentioning
confidence: 99%